Faktor - Faktor yang Memengaruhi Kepatuhan Membayar Iuran Jaminan Kesehatan Nasional oleh Peserta Pekerja Bukan Penerima Upah di Kota Jakarta - Singgih Aji Pangestu; Sarah Geltri Harahap; Hardin La Tamba (Pusat riset dan Inovasi Nasional, 2026)
Compliance in paying contributions is an important factor in ensuring the sustainability of the National Health Insurance (JKN) program, especially in the Non-Wage Workers (PBPU) segment who make payments independently. However, the level of compliance of PBPU participants in Jakarta City is still low, as indicated by the high rate of contribution arrears and the large number of deactivated memberships. This study aims to analyze the factors that influence compliance in paying National Health Insurance (JKN) contributions in the Non-Wage Workers (PBPU) segment in Jakarta City in 2025. The research design used was quantitative with a cross-sectional approach, involving 180 respondents. Bivariate analysis using the Chi-Square test showed that there was a significant relationship between perception and compliance (p = 0.002), income with compliance (p = 0.046), and motivation with compliance (p = 0.000). However, there was no significant relationship between knowledge (p = 0.291) and sanctions (p = 0.103) on compliance in paying contributions. These findings indicate that psychological and economic aspects have a strong influence on driving compliance with JKN premiums. Therefore, efforts to improve compliance need to focus on enhancing positive perceptions, internal motivation, and sustainable income for participants. Perception is the most dominant factor influencing compliance among PBPU participants. Strategies to increase education and improve services are needed to boost compliance and ensure the sustainability of the JKN program.